2012
DOI: 10.1111/j.1751-7176.2012.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Primary vs Secondary Hypertension in Children

Abstract: Despite current guidelines, variability exists in the workup of hypertensive children due to physician preferences. The study evaluates primary vs secondary hypertension diagnosis from investigations routinely performed in hypertensive children. This retrospective study included children 5 to 19 years with primary and secondary hypertension. The proportions of abnormal laboratory and imaging tests were compared between primary and secondary hypertension groups. Risk factors for primary vs secondary hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 31 publications
6
39
0
2
Order By: Relevance
“…[7,8] This is consistent with prior research suggesting primary care pediatricians are uncomfortable in treating and managing pediatric hypertension. [10,11] However, the “refer all” approach is unlikely to be sustainable by pediatric cardiology or pediatric nephrology workforce, and it is a source of frustration for some pediatric hypertension specialists.…”
Section: Introductionsupporting
confidence: 83%
“…[7,8] This is consistent with prior research suggesting primary care pediatricians are uncomfortable in treating and managing pediatric hypertension. [10,11] However, the “refer all” approach is unlikely to be sustainable by pediatric cardiology or pediatric nephrology workforce, and it is a source of frustration for some pediatric hypertension specialists.…”
Section: Introductionsupporting
confidence: 83%
“…However, a direct correlation between hypertensive encephalopathy and renal disease has not been proven. Unlike other etiologies, hypertension originating from renal disease could cause severe hypertension by complex mechanisms, such as renin angiotensin system activation, fluid overload, activated sympathetic tone, and an electrolyte imbalance15,16). This study showed that the renal origin hypertension group had higher mean blood pressure than the nonrenal origin hypertension.…”
Section: Discussionmentioning
confidence: 63%
“…Secondary hypertension is more common in younger children resulting from reno-vascular or renal parenchymal disease (78–80% of causes) (14, 15), endocrine (11% of causes) (14), cardiac (2% of causes) (16), pulmonary and others as shown in Table 1. Since PCCs and PGLs account for only 0.5–2% (2) of secondary hypertension, one should be mindful to rule out more common causes when evaluating a child with elevated blood pressure (BP).…”
Section: Causes Of Hypertension In Pediatricsmentioning
confidence: 99%